Immune response of broilers fed conventional and alternative diets containing multi-enzyme complex - Montanhini Neto,R (2013)
The present study aimed at evaluating the effect of adding a commercial multi-enzyme complex to conventional and alternative broiler diets on the immune response and occurrence of lesions in the intestinal mucosa. In total, 900 male broiler chicks were distributed according to a completely randomized design, with six treatments of six replicates each. Two control diets were formulated: one with conventional feedstuffs (T1), based on corn and soybean meal, and one with alternative feedstuffs (T4), containing corn, millet, and soybean, canola and sunflower meals. Based on these diets, other four were prepared with reduced metabolizable energy, digestible amino acids, calcium and available phosphorus levels and the addition (T3 and T6) or not (T2 and T5) of a multi-enzyme complex. Broilers fed diets based on conventional feedstuffs had higher levels of defense cells compared with those fed diets that included millet with canola and sunflower meals. On the other hand, the use of enzymes in conventional or alternative diets decreased the number of these cells in the ileal mucosa.